Culture and Congruence: The Fit Between Management Practices and National Culture - Newman, Karen L.; Nollen, Stanley D. (Journal of International Business Studies, 1996)
The financial performance of European and Asian work units of one multinational company is examined as a function of the congruence between management practices and national culture. Using Hofstede's five national culture dimensions and analogous management practices, we find that work unit financial performance is higher when management practices in the work unit are congruent with the national culture.